Perancangan Value Proposition, Business Model Canvas, Proses Bisnis dan Aplikasi Plasma Darah Konvalesen - Imanuela Alesia Santoso; Felecia Felecia (Jurnal Titra, 2022)
Plasma can be used to treat people with critical Covid-19 symptoms. There’s a supply shortage of plasma, so it’s difficult to obtain plasma in a short time. Value propositions, BMC, and business processes needs to be designed to connect donors seeker, donors, and PMI, so that the plasma can be obtained easily and quickly.  This application will automatically connects the perfect donors to the Covid patients who need plasma. It acts as a connector, so that the donors can immediately donated their plasma for their matched patient. Donors can do an online registration through this application, so they don’t need to do a manual registration at PMI. This application provides all information about the donors status and the donor flows, so the donor seekers are able to check the donor processes any time. This application is able to save time and energy, there is transparent information about the donor processes and the donor schedule. The value propositions, BMC, and business processes have been verified and validated through interview with the donor seekers, donors, non-donors, and PMI. They stated that this application is easy to understood, makes the search and donor easier, and can be applicated in PMI.